EXPERIMENTAL RESEARCH ON ULTRASONIC WELDING - Cornelia LUCHIAN; Delia GÂRLEANU; Gabriel GARLEANU; Florea DUMITRACHE (Fiabilitate şi Durabilitate, 2012)
This paper presents the optimum ultrasound welding parameters of copper sheets usingstatic analysis methods results and microscopic structural analysis. Also it get the conclusion thatweld formation it’s produced after the plastic deformation process of metals because the action ofultrasonic energy in the joint area.